A robust computational framework for estimating 3D Bi-Atrial chamber wall thickness. (November 2019) - Wang, Yufeng; Xiong, Zhaohan; Nalar, Aaqel; Hansen, Brian J.; Kharche, Sanjay; Seemann, Gunnar; Loewe, Axel; Fedorov, Vadim V.; Zhao, Jichao
Abstract: Atrial fibrillation (AF) is the most prevalent form of cardiac arrhythmia. The atrial wall thickness (AWT) can potentially improve our understanding of the mechanism underlying atrial structure that drives AF and provides important clinical information. However, most existing studies for estimating AWT rely on ruler-based measurements performed on only a few selected locations in 2D or 3D using digital calipers. Only a few studies have developed automatic approaches to estimate the AWT in the left atrium, and there are currently no methods to robustly estimate the AWT of both atrial chambers. Therefore, we have developed a computational pipeline to automatically calculate the 3D AWT across bi-atrial chambers and extensively validated our pipeline on both ex vivo and in vivo human atria data. The atrial geometry was first obtained by segmenting the atrial wall from the MRIs using a novel machine learning approach. The epicardial and endocardial surfaces were then separated using a multi-planar convex hull approach to define boundary conditions, from which, a Laplace equation was solved numerically to automatically separate bi-atrial chambers. To robustly estimate the AWT in each atrial chamber, coupled partial differential equations by coupling the Laplace solution with two surface trajectory functions were formulated and solved. Our pipeline enabled the reconstruction and visualization of the 3D AWT for bi-atrial chambers with a relative error of 8% and outperformed existing algorithms by >7%. Our approach can potentially lead to improved clinical diagnosis, patient stratification, and clinical guidance during ablation treatment for patients with AF. Highlights: A novel computational pipeline is proposed for calculation of atrial wall thickness. A coupled PDE approach is proposed to produce wall thickness to guide targeted treatment for atrial fibrillation. Fully automated workflow includes deep learning and Laplace-based solutions. Proposed pipeline outperforms other methods of automated thickness estimation. Proposed pipeline is efficient and produces accurate thickness estimation.